Investigation of the tunneling properties and surface morphologies of BaSi2/Si tunnel junctions for BaSi2 solar cell applications. Issue 12 (25th November 2013) - Du, Weijie; Baba, Masakazu; Takabe, Ryota; Zhang, Ning; Toko, Kaoru; Usami, Noritaka; Suemasu, Takashi; Maeda, Yoshihito; Suzuki, Motofumi
Abstract Three different tunnel junctions (p+‐BaSi2/p+‐Si, n+‐BaSi2/p+‐Si and n+‐BaSi2/n+‐Si) have been fabricated for the formation of BaSi2 solar cells on Si substrates. Investigation of the tunneling properties and surface morphologies of these tunnel junctions has been done to find out which one is the best. From the current‐voltage characteristics, p+‐BaSi2/p+‐Si tunnel junction showed the greatest current of the three. The surface morphologies revealed that the p+‐BaSi2/p+‐Si tunnel junction has a very smooth surface compared with the other tunnel junctions. Tunnel junction with a smooth surface is a requirement for growing BaSi2 overlayers for BaSi2 solar cells. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)